Evaluation of Landsat 8 OLI imagery for unsupervised inland water extraction. Issue 8 (17th April 2016) - Xie, Huan; Luo, Xin; Xu, Xiong; Pan, Haiyan; Tong, Xiaohua
ABSTRACT: The successful launch of the Landsat 8 satellite continues the Earth observation of the Landsat series, which has been taking place for nearly 40 years. With the increase in the band number and the improved spectral range compared with the previous Landsat imagery, it will be possible to expand the application of the new Landsat 8 imagery. The purpose of this study is to explore water extraction based on the new Landsat 8 Operational Land Imager (OLI) imagery. According to the specific inland water conditions (clear water, turbid water, and eutrophic water), a number of highly adaptable water indices are assessed for water extraction using Landsat OLI imagery. The results show that clear water is the easiest to extract among the different types of waterbodies, with the highest average accuracy of 97%. The highest-accuracy methods are the automated water extraction index for shadow pixels (AWEIsh ), the normalized difference water index using bands 4 and 7 (NDWI47 ), and the normalized difference water index using bands 3 and 7 (NDWI37 ), with accuracies of 98.55%, 95.50%, and 96.61%, corresponding to clear water, turbid water, and eutrophic water, respectively. Through the analysis of the different methods for optimal band selection, the seventh band OLI7 (shortwave infrared 2, SWIR-2) of Landsat OLI shows the best performance in water identification. When applying the water indices to water extraction, Otsu's algorithm has been used to automatically select the water threshold. Using extensive experiments with Otsu's algorithm and a manual method, it was found that Otsu's algorithm can replace manual selection and has the ability to select an accurate threshold for water extraction.